Global Economic Prospects : Financial Market Outlook, July 2013 - Aykut, Dilek (World Bank, Washington, DC, 2015)
Global financial markets were largely stable during the past year, not with-standing the recent uptick in volatility amid uncertainty over the timing of an eventual tapering off of quantitative easing. Improved financial conditions are reflected in a strong rebound in gross capital flows (international bond issuance, cross-border syndicated bank loans and new equity placements) to developing countries, which were 63 percent higher in the first five months of 2013 than during the same period in 2012. Foreign direct investment (FDI) inflows to developing countries increased by 9 percent during the first quarter of 2013 on a year-on-year basis, with a mixed picture across countries. Since late May, financial market volatility has increased, with increased expectations about possible tapering of U.S. quantitative easing in coming months and uncertainty over its impacts. Although there have been some large stock market corrections in some Asian countries, so far the overall impact has been moderate. Bond yields on developing country debt are also on the rise as base rates and spreads increase.